Identifikasi Citra Kuku Identifikasi Citra Kuku Anak Kembar Identik Berbasis Jaringan Saraf Tiruan Menggunakan Metode Learning Vector Quantization - Apit Suryanto (JMAI (Jurnal Multimedia & Artificial Intelligence), 2021)
Twins have many similarities in common, both physically and psychologically. Similarities are what make twins look unique compared to other individuals. Most people find it difficult to distinguish between physically similar twins. A twin identification system can be implemented to help users distinguish between twins. The technology used in this study was an identification system based on fingernail images. This application was made by the Learning Vector Quantization method to perform fingernail image recognition in twins. The results showed that the application could recognize images with an accuracy rate of 100%. This application is expected to simplify users to distinguish between the brothers and sisters in twins. Keywords : Twins, Fingernail Images, Learning Vector Quantization